2007
DOI: 10.1002/pola.21995
|View full text |Cite
|
Sign up to set email alerts
|

New stage in living cationic polymerization: An array of effective Lewis acid catalysts and fast living polymerization in seconds

Abstract: Our recent extensive research on Lewis acid catalysts with a weak base for the cationic polymerization of vinyl ethers led to unprecedented living reaction systems: fast living polymerization within 1-3 s; a wide choice of metal halides containing Al, Sn, Fe, Ti, Zr, Hf, Zn, Ga, In, Si, Ge, and Bi; and heterogeneously catalyzed living polymerization with Fe 2 O 3 . The use of added bases for the stabilization of the propagating carbocation and the appropriate selection of Lewis acid catalysts were crucial to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
76
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 75 publications
(115 reference statements)
1
76
0
Order By: Relevance
“…As the number average molar mass increased, the crystallinity of the polymers and the number of crystallizable carbon atoms in the side chains of PC 14 E 1 VE and PC 14 E 2 VE were all reduced. The results were consistent with the previously reported literature [26,28]. For PC 14 E n VE, when n changed from 1 to 2, the number of crystallizable CH 2 groups N c were increased but the crystallinity of the polymers X c was decreased simultaneously.…”
Section: Structure Of Poly(mono/diethylene Glycol N-tetradecyl Ether supporting
confidence: 82%
See 1 more Smart Citation
“…As the number average molar mass increased, the crystallinity of the polymers and the number of crystallizable carbon atoms in the side chains of PC 14 E 1 VE and PC 14 E 2 VE were all reduced. The results were consistent with the previously reported literature [26,28]. For PC 14 E n VE, when n changed from 1 to 2, the number of crystallizable CH 2 groups N c were increased but the crystallinity of the polymers X c was decreased simultaneously.…”
Section: Structure Of Poly(mono/diethylene Glycol N-tetradecyl Ether supporting
confidence: 82%
“…These polymers PC 14 E n VEs (n = 1, 2) were measured using gel permeation chromatography (GPC) in THF at room temperature. The results are listed in In order to further analyze the impact of different molecular weights on the crystallization properties of polymers, the crystallinity of polymers and the number of crystallizable carbon atoms per side chain were calculated by Equations (1)- (3) [26,27]:…”
Section: Structure Of Poly(mono/diethylene Glycol N-tetradecyl Ether mentioning
confidence: 99%
“…[15][16][17] One of the methods that allows living cationic polymerization is the base-assisting reaction with a Lewis acid. [18][19][20] Recently, we have reported a series of greatly-improved living cationic polymerization systems of VE and St derivatives in the presence of an added Lewis base. [19][20][21] For example, it was demonstrated that various Lewis acids, including nonconventional ones, could act as living cationic polymerization catalysts in conjunction with an appropriate added Lewis base.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Recently, we have reported a series of greatly-improved living cationic polymerization systems of VE and St derivatives in the presence of an added Lewis base. [19][20][21] For example, it was demonstrated that various Lewis acids, including nonconventional ones, could act as living cationic polymerization catalysts in conjunction with an appropriate added Lewis base. 22 Furthermore, this procedure permitted successful living polymerization of some monomers [23][24][25] that were previously considered to be challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Attempted cycloheptene formation also failed with both enolizable (dimethyl) and non-enolizable (diphenyl) substrates (Table 2, entries 5 and 6). Finally, an intermolecular Rauhut-Currier reaction with methyl vinyl ketone and tin tetrachloride lead only to products of polymerization (not shown); not surprising given the prevalence of cationic polymerization practices 10 . In pursuit of complex natural product-like intermediates for the generation of potentially bioactive compounds, we also explored the use of Lewis acids for Rauhut-Currier formation on a more complex substrate, 5 (see Supporting Information for synthesis of 5).…”
mentioning
confidence: 99%